Social activity as a mediator between childhood adversity and depressive symptoms in middle-aged and older Chinese adults - Wu, Ping; Ding, Jinqi; Jin, Haiying; Zhang, Junhang; Greenshaw, Andrew J.; Liang, Sugai (Frontiers in Psychiatry, 2025)
BackgroundAdverse childhood experiences (ACEs) are associated with an increased risk of depressive symptoms (DS) in older adults. This study investigated the role of social activity in mediating the relationship between ACEs and DS among middle-aged and older Chinese adults.MethodsData were derived from the China Health and Retirement Longitudinal Study (CHARLS). The discovery dataset included 10,164 participants from 2018, matched with life history data from 2014, while the replication dataset comprised 8,899 participants from 2020. DS was measured using the Center for Epidemiologic Studies Depression Scale (CES-D). Multiple linear regression and mediation analysis were conducted.ResultsIn the discovery dataset, ACEs were positively correlated with DS (r = 0.17, p < 0.001), while social activity was negatively correlated with both DS (r = –0.11, p < 0.001) and ACEs (r = –0.03, p = 0.01). Mediation analysis indicated that ACEs significantly predicted DS (estimate = 0.51, 95% CI 0.43 to 0.60), and social activity partially mediated this relationship (estimate = –0.01, bootstrap 95% CI –0.01 to –0.001), particularly among middle-aged adults (indirect effect estimate = –0.01, bootstrap 95% CI –0.01 to –0.001). Additionally, social activity notably mediated the relationship between childhood violence exposure and DS (estimate = –0.02, bootstrap 95% CI –0.04 to –0.003). These results were robustly validated through replication analysis, reinforcing the reliability of our conclusions.ConclusionsSocial activity mediates the relationship between ACEs and DS, highlighting the importance of social engagement to reduce depression risk in this population.